The Changing Face of Craniopharyngioma Treatment in Young Children and its Challenges at a Single Centre in a Developing World Context - Mankahla, Ncedile (Division of Neurosurgery, 2020)
Objective: To retrospectively review our institutional experience with the treatment of paediatric craniopharygiomas and assess the evolution in management and influence on patient outcomes. Patients and Methods: A retrospective review from January 1995 to December 2015 of children age <14 treated at a single institution. Data collected included admission clinical features, endocrine function, surgery performed, surgical outcome, intracystic therapy and radiotherapy. Long-term functional outcome was calculated considering hormonal dependence, level of independence and schooling. Results: There were 41 patients with a mean age of 84.2 months: 57% were female. Primary surgical resection was performed in 36 patients: 80.5% had subtotal resection, 11% had gross total resection and the rest had biopsy only. Of surgical approaches, 60,7% had pterional craniotomy and 39,2% supraorbital keyhole craniotomy. No surgical mortalities occurred but 2 patients had new post-operative neurological deficits. Stereotactic placement of intracystic catheters transitioned to endoscopic. Intracystic treatments transitioned from Yttrium (1) to Bleomycin (6) to Interferon Alpha (6). Radiotherapy was given in 30 patients, median dose 54Gy. Final Wen functional outcome was 21,8% Class I, 32% Class II and 46% Class III. There were no early deaths in the series but 5 patients died more than 6 years after diagnosis, mostly due to endocrine crises from poor chronic care. Conclusion: The findings reflect a multidisciplinary team approach consisting of maximal safe resection with radiotherapy, intracystic agents and endocrine support. For a cohort limited to young children, our results are similar in number and outcomes to other published series. Mortality remains low but lifelong dependence on endocrine replacement is a significant contributor to long-term morbidity and mortality. This has important implications for patients referred from large distances and where primary and secondary follow up care is poor.